Упростить выражение 1-cos x*1+cosx/sin^2*x sin2*пи+a+cosпи+a+ sin-a+cos-a и также решить уравнение 8sinx-cos x=0 3tg^2*x+2tgx-1=0 cos 5x=cos 3x sin 9x

1 Январь 0001



упростить выражение (1-cos x)*(1+cosx)/(sin^2*x) sin(2*пи+a)+cos(пи+a)+ sin(-a)+cos(-a) и также решить уравнение 8sinx-cos x=0 3tg^2*x+2tgx-1=0 cos 5x=cos 3x sin 9x-sin x=cos 5x зарание спасибо

  • (1-сosx)(1+cosx)/sin^2x  =  (1 – cs^2x)/sin^2x  =  sin^2x/sin^2x  =  1

    sin(2*pi +a) + cos(pi + a) + sin(-a) + cos(-a)  =  sina – cosa -sina + cosa  =  0



     



    8sinx-cosx = 0  Разделим  почленно  обе  части  ур-ия  на  сosx   неравен  нулю.

    8tgx – 1 = 0,    8tgx = 1,   tgx  =  1/8 —–> x = arctg 1/8 + pi *n,  где  n принадлежит  Z

     

    3tg^2 x  +  2tgx  -1  =  0

    заменим  tgx = t    tg^2 x  =  t^2  Получим

    t^2  +  2t  -  1  =  0

    D  =  b^2 – 4ac = 2^2 – 4*1*(-1) = 4 + 4 = 8

    t_1 = (-b + VD)/2a  =  -2  +  V8 = -2+2V2

    t_2 = (-b-VD)/2a     = -2   -   V8  =  -2 – 2V2

    tgx = -2+2V2         x_1  =  arctg(-2+2V2)  +  pi*n,  где  n  принадлежит  Z

    tgx = -2-2V2          x_2  =  arctg(-2-2V2)    + pi*n









Алгебра

Комментарии закрыты.